ANALYSIS OF CRACK-LIKE FLAWS ON A WELD JOINT OF A CYLINDRICAL PRESSURE VESSEL BASED ON API 579-1 STANDARD - Kristianto, Yonathan
The oil and gas industry plays an important role in the fulfilment of domestic energy. The reliability of oil and gas production are needed to ensure energy supply. In reality, failures can occur in a production equipment that can disrupts the energy supply. One of the production equipment used in the oil and gas industry are a pressure vessel. Failure in pressure vessels can happened because of the cracks in the weld joint of the vessel. To determine the operational fitness of a pressure vessel that contains cracks, a crack assessment method is needed. Fitness-For-Service (FFS) is a method that can be used to determine the operational fitness of pressurized equipment that contains flaws. One of the standards used in the FFS assessment is API 579-1. There are three levels of assessment that can be performed using the API 579-1 standard. In this research, a case study was conducted to determine the operational fitness of a cylindrical pressure vessel with cracks. Cracks were modelled to occur in the weld joint between the head and the nozzle of the pressure vessel. There were several crack configurations being modelled. The assessment was carried out based on the level 3 method B assessment procedure which can be found in the API 579-1 Part 9 standard. From the assessment results, all crack configurations were below the failure assessment diagram’s boundary curve. Based on these results, the pressure vessel was declared fit to continue operating, even though one crack configuration was found in the pressure vessel.